Examining Institutional-Level Factors and Campus Climate on Sexual Misconduct Reporting to Title IX Coordinators and in Annual Security Reports - Richards, Tara N. (Victims & offenders, 2024)
The present study examines the relationship between institutional-level factors and perceptions of campus climate and rates of sexual misconduct reporting to Title IX coordinators and in Annual Security reports. Data is drawn from public 4-year institutions of higher education (IHEs), community colleges, and independent IHEs in Maryland (n = 42) from 2018 to 2020. Regarding institutional level factors, higher residentiality, higher percentages of graduate students and students supported by Pell grants, and higher rates of alcohol and drug use violations were associated with higher rates of sexual misconduct reporting. On campus climate measures, only higher percentages of students reporting they know whom to contact to report sexual misconduct was associated with increased reporting. Implications for sexual misconduct prevention training and the integration of alcohol and drug use prevention into sexual misconduct prevention education are discussed. Directions for future research are also outlined.